Construction and characterizations of hollow carbon microsphere@polypyrrole composite for the high performance supercapacitor. (August 2018) - Lu, Qun; Liu, Jia; Wang, Xianyou; Lu, Bing; Chen, Manfang; Liu, Meihong
Graphical abstract: Preparation and characterization of the hollow carbon microsphere@polypyrrole (HCS@PPy) composite via chemical oxidation polymerization for the supercapacitors. Highlights: The hollow carbon microsphere@polypyrrole (HCS@PPy) composite has been designed, synthesized through in situ chemical oxidation polymerization. The HCS@PPy composite possesses fluffy PPy thin layer with thickness of 17 nm and keeps perfect spherical morphology. High specific capacitance of 508 F/g at 1 A/g is obtained for the HCS@PPy composite. The asymmetrical supercapacitor based on HCS@PPy composite shows a high energy density of 46 Wh/kg at 350 W/kg and the energy density still maintains at 19.6 Wh/kg at a high power density of 5600 W/kg. Abstract: The hollow carbon microsphere@polypyrrole (HCS@PPy) composite has been designed, synthesized through in situ chemical oxidation polymerization, and used as the active electrode material of supercapacitor. The porous structure, morphology and supercapacitive behaviors of the HCS@PPy composite are investigated by various physical characterization techniques and electrochemical measurement. The results show that HCS has the lychee-like hollow spherical morphology, and a fluffy PPy thin layer with thickness of 13 nm is uniformly coated on the surface of the HCS. The HCS@PPy composite reveals a high specific capacitance of 508 F/g at 1 A/g since it is the combination of both double-layer capacitances of HCS and faradic capacitance of PPy. The supercapacitor using HCS@PPy composite as the active material delivers excellent rate performance and outstanding cycle stability. Furthermore, the asymmetrical supercapacitor based on the HCS@PPy composite shows a high energy density of 46 Wh/kg at the power density of 350 W/kg. The improved supercapacitive performance is closely related with the integrated advantage of unique hollow porous structure of HCS and faradaic redox behavior of PPy, indicating that the design and preparation of HCS@PPy composite is a promising strategy for active material of high performance supercapacitor.